The Duelling Debate in Latin America, 1870-1920: Repress, Legalise, or Just Look the Other Way? - Parker, D. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1998)
AbstractAlthough formally considered a crime, the duel became increasingly common in Latin America through the late nineteenth and early twentieth centuries, especially among the political class, the very people charged with writing, interpreting, and enforcing the laws. The contradiction was not lost on contemporaries, who saw the impunity of duelling as a serious problem and debated how best to overcome the gulf between law and practice. This article looks at the arguments for and against the criminalisation of the duel, and shows how the debate raised far more fundamental questions about the role of law in a modernising society.